Magical realism in West African fiction : seeing with a third eye - Cooper, Brenda (Routledge, 1998)
This study contextualizes magical realism within current debates and theories of postcoloniality and examines the fiction of three of its West African pioneers: Syl Cheney-Coker of Sierra Leone, Ben Okri of Nigeria and Kojo Laing of Ghana. Brenda Cooper explores the distinct elements of the genre in a West African context, and in relation to: * a range of global expressions of magical realism, from the work of Gabriel Garcia Marquez to that of Salman Rushdie * wider contemporary trends in African writing, with particular attention to how the realism of authors such as Chinua Achebe an.
Keywords: Cheney-Coker, Syl, -- 1945- -- Criticism and interpretation.; Laing, B. Kojo -- Criticism and interpretation.; Okri, Ben -- Criticism and interpretation.; Cheney-Coker, Syl, -- 1945-; Laing, B. Kojo; Okri, Ben; West African fiction (English) -- History and criticism.; Postcolonialism -- Africa, West.; Postcolonialism in literature.; Africa, West -- In literature.; Magic realism (Literature); Roman ouest-africain (anglais) -- Histoire et critique.; Postcolonialisme -- Afrique occidentale.; Postcolonialisme dans la littérature.; Afrique occidentale -- Dans la littérature.; Réalisme magique (Littérature); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Literature; Postcolonialism; Postcolonialism in literature; West African fiction (English); West Africa; Fictie.; Engels.; Magisch realisme.; West-Afrika.; Criticism, interpretation, etc.